Exploring the Link Between the Gut Mycobiome and Neurological Disorders - Ali Yetgin (Advanced Gut & Microbiome Research)
Long-standing theories link genetics, environmental factors, and microbial dysbiosis as causes of neurological diseases. Even though the role of the human gut mycobiome in these disorders has drawn a lot of attention, recent research has begun to shed light on another microbial component, the gut mycobiome, and its potential involvement in neurological diseases. In an effort to comprehend the connection between the gut mycobiome and neurological illnesses, this exploratory investigation concentrates on the complex interactions between fungal populations and the central nervous system. This study investigates the mechanisms through which fungus species and their metabolites impact brain health and disease progression by evaluating the body of literature and recent discoveries. It also investigates how the gut mycobiome affects the blood–brain barrier’s integrity, the control of neurotransmitters, and immune system modulation. The outcomes provide new information on therapeutic approaches that target the fungal component of the gut microbiota and imply that changes in the composition and function of the gut mycobiome contribute to the onset and progression of neurological diseases. It is necessary to conduct more studies to clarify the precise mechanisms underpinning the gut mycobiome’s impact on neurological illnesses and to investigate the possibility of new diagnostic and therapeutic approaches based on fungus modulation.